Final Syllable Reduction in Middle Indic and Iranic - Ollett, Andrew (Bhasha, 2024)
The mutual influence of Indic and Iranic languages in the ‘contact zone’ of the upper Indus valley and the adjoining mountain ranges has long been known to scholarship. Previous scholarship has observed lexical borrowings in the ancient period, and phonological and morphological features in the modern period. Outside of this area, the Indic and Iranic languages developed in different ways, largely in accordance with the prominence of the syllable and the word, respectively, in their phonologies. The important Middle Indic languages of Gandhari and Apabhramsha, however, appear to have participated in certain structural changes that affected all of the contemporary Middle Iranic languages, above all the reduction of final syllables. The fact that the earliest attestation of these changes in Middle Indic occurs in languages strongly associated with the Indo-Iranian contact zone suggests that contact may have played a critical role. The chronology of these changes in Middle Indic also suggests that they occurred in the ‘Saka-Kuṣāṇa Age’ in the early centuries of the common era.